Thinking with an Accent: Toward a New Object, Method, and Practice - Pooja Rangan; Akshya Saxena; Ragini Srinivasan; Pavitra Sundar (University of California Press, 2023)
Thinking with an Accent casts accent as a powerfully coded yet underexplored mode of perception shaping our global cultural economy. Theorizing accent as a mediatized object, an interdisciplinary method, and an embodied practice, this volume invites readers to think with an accent—to practice a dialogical, multisensorial inquiry that can yield transformative modalities of knowledge, action, and care. "There is no such thing as a voice without an accent, yet theories of voice still treat accents as the exception. Thinking with an Accent teaches us how to begin from accented voices and provides a panoply of tools for imagining, working with, building on, analyzing, and desiring accents." — JONATHAN STERNE, author of Diminished Faculties: A Political Phenomenology of Impairment "This creative and ambitious collection encourages us to reconsider our own accented lives and how they structure our social, digital, and literary worlds. An essential book." — DOLORES INÉS CASILLAS, author of Sounds of Belonging: U.S. Spanish-Language Radio and Public Advocacy "This book teaches us that the accent must be understood not as an ontological reality but as a co-constituted happening. The result is that accent becomes something to think with, not just to study. Straightforward, well argued, and a pleasure to read." — KAREEM KHUBCHANDANI, author of Ishtyle: Accenting Gay Indian Nightlife"
Keywords: 300; Accent